2022
DOI: 10.1002/pc.27164
|View full text |Cite
|
Sign up to set email alerts
|

Microwave absorption and bending properties of three‐dimensional gradient honeycomb woven composites

Abstract: To avoid the narrow absorption bandwidth and delamination in uniform honeycomb composites, three-dimensional (3D) gradient honeycomb composites were prepared through a vacuum-assisted resin transfer molding (VARTM) process. The 3D gradient honeycomb woven composite (3D GHWC) was made by using 3D gradient woven fabric with basalt and carbon fibers as reinforcement and epoxy resin mixed with carbon black and carbonyl iron powder as the matrix. For further optimization of the effective absorbing bandwidth and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…3D (three-dimensional) woven fabrics have been considered structurally robust 20,21 and are expected to serve as wearable EM-wave absorption fabric due to the tailorable 3D structures. 22 For instance, Zhang et al fabricated a 3D gradient honeycomb-woven composite (3D GHWC) using basalt and carbon fibers as reinforcement and the carbon blackcarbonyl iron powder-modified epoxy as the resin matrix. The average bending strength of these 3D GHWC reached 101.7 MPa, and the microwave absorption performance was −47 dB at a thickness of 18.5 mm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D (three-dimensional) woven fabrics have been considered structurally robust 20,21 and are expected to serve as wearable EM-wave absorption fabric due to the tailorable 3D structures. 22 For instance, Zhang et al fabricated a 3D gradient honeycomb-woven composite (3D GHWC) using basalt and carbon fibers as reinforcement and the carbon blackcarbonyl iron powder-modified epoxy as the resin matrix. The average bending strength of these 3D GHWC reached 101.7 MPa, and the microwave absorption performance was −47 dB at a thickness of 18.5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhang et al fabricated a 3D gradient honeycomb-woven composite (3D GHWC) using basalt and carbon fibers as reinforcement and the carbon black-carbonyl iron powder-modified epoxy as the resin matrix. The average bending strength of these 3D GHWC reached 101.7 MPa, and the microwave absorption performance was −47 dB at a thickness of 18.5 mm . However, the trade-off between rigid bulk EM-wave absorber and wearable fabric substrate still hindered its application in smart wearable electronics; it remains challenging to optimize versatile functions, i.e., impedance matching with fabric substrate, EM-wave absorption, and wearability (good mechanical strength, flexibility, and air permeability), in a functional fabric.…”
Section: Introductionmentioning
confidence: 99%
“…Another EOG/CIP composite with 0.5 wt.% EOG and 72 wt.% CIP and a thickness of 1.33 mm reached an RL min of −69.27 dB at 15 GHz with an EAB of 6.47 GHz. Furthermore, CIP and other nanomaterials have been incorporated into special three-dimensional structures, such as gradient structures, honeycomb structures, topological structures, foam structures, multilayer structures, biomimetic structures, and vertically oriented structures, to enhance electromagnetic absorption performance [16][17][18][19][20][21][22][23][24][25][26][27][28]. Honeycomb structure absorbing composites are a significant research focus in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the above structural weakness of the common 2D MA fabrics, numbers of 3D woven fabrics have been reported that are structurally strong and lightweight [24][25][26] and can serve as the enhanced MA absorbers due to the established 3D microwave absorbing networks within those fabrics [27,28]. For instance, Zhang et al fabricated a series of 3D gradient honeycomb woven composites (3D GHWC) with the basalt and carbon fibers as reinforcement and the carbon black-carbonyl iron powder-modified epoxy as the resin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhang et al fabricated a series of 3D gradient honeycomb woven composites (3D GHWC) with the basalt and carbon fibers as reinforcement and the carbon black-carbonyl iron powder-modified epoxy as the resin matrix. The average bending strength of these 3D GHWC reaches 101.7 MPa and the optimal RL min value is -47 dB in the C band for a 18.5 mm thick 3D GHWC specimen tested using an Agilent vector network analyzer at the incident angle of 30° [27]. In addition, Xie et al reported the MA properties of the gypsum filled 3D woven fabric composites with the CB particles (0-3 wt.%) as the microwave absorbent.…”
Section: Introductionmentioning
confidence: 99%